INTEGRATION OF ROBOT-WSN FOR ANIMAL ACTIVITY MONITORING IN AGRICULTURAL FIELDS WITH IOT IMPLEMENTATION - Suresh, Banoth; Hathiram, Easlavath; Chilla, Divya (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
An agricultural nation's development is mostly dependent on agriculture. Agriculture-related problems have long impeded the nation's progress. Modernising the current conventional agricultural processes with smart agriculture is the only way to solve this problem. Thus, the project's goal is to use IOT technologies and robots with wireless sensor networks to monitor the actions of animals and birds in agricultural fields. These robots live beside sensors and work together to accomplish a task by imposing hardware limitations. A robotic wireless sensor network is described as an autonomous multi-robot system networked together with specific sensing objectives. Three robots are wirelessly connected in our project using NRF24L01 wireless transceivers. deploying the best sensor possible in an agricultural area to transmit a signal that can identify the position of an animal. The closest robot then assumes command and launches an assault on the field animal. These robots are interacting with one another, and one robot is utilising GPRS to transfer the data from all three robots to a cloud database. Through the use of a web application, users can watch cloud data, and then utilise an ultrasonic repellent to terrify animals and birds depending on precise, real-time field data. All of these tasks will be managed by integrating sensors, NRF24L01 modules, and microcontrollers, and they will all be controlled by any distant smart device or computer with an Internet connection.